PENDAMPINGAN KEWIRAUSAHAAN SOSIAL BERBASIS DANA SOSIAL KEAGAMAAN DI DESA SUKANEGARA JONGGOL JAWA BARAT - Khoirun Nisa; Nur Izzah; Mia Indriyani; Aulia Utami Aripin (DEVELOPMENT: Journal of Community Engagement, 2022)
Micro, Small, and Medium Enterprises (MSMEs) in Desa Sukanegara Jonggol Jawa Barat face significant challenges in management, marketing, and access to capital, hindering their economic independence. This community service activity aims to address these problems through a social entrepreneurship mentoring model integrated with the utilization of social funds as productive capital. The implementation method uses a participatory approach consisting of needs analysis, mentoring implementation, and monitoring and evaluation. Mentoring materials included changing the social entrepreneurship mindset, financial management, product innovation, and digital marketing. The results showed a significant increase in the managerial capacity and technical skills of MSME actors, as well as an increase in income and market expansion. This mentoring model proved effective in transforming social funds from consumptive aid into productive investment, thus encouraging the sustainable economic independence of MSMEs.